RESPON BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) TERHADAP PEMBERIAN PUPUK DAUN DAN GIBERELIN - Jefri Rudiansyah; Nurbaiti Nurbaiti; Gunawan Tabrani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aims to determine the responses of oil palm seedlings (Elaeis guineensis Jacq.) those grow better with foliar fertilizer and gibberellins. This study was  a 3 x 3 factorial experiment arranged in completely randomized design (CRD), consists of two factors and three replications. The first factor is the concentration of foliar fertilizer (D), which consists of three levels ie d0 = without foliar fertilizer (0 ppm), d1 = 1.500 ppm concentration of foliar fertilizer and foliar fertilizers d2 = concentration of 3.000 ppm. The second factor is the concentration of gibberellins (G) which consists of three levels ie g0 = without giberelin (0 ppm), g1 = giberelin concentration of 5.000 ppm and g2 = giberelin concentration of 10.000 ppm. Data were statistically analyzed using analysis of variance and orthogonal contrast test at the 5 % level. Parameters those observed were seedling height, number of leaf midrib, stump diameter, root mass, root to shoot ratio, seedling dry weight and seedling quality index. The results showed that there was no interaction effect of foliar fertilizer with gibberellins on growth component of oil palm seedlings on variables: height, number of leaf midrib, stump diameter, root volume, ratio canopy root, seedling dry weight and seedling quality index. Gibberellins treatment increases the height of oil palm seedlings, compared with those not given giberelin while leaf fertilizer treatment did not increase the height of the plant. Seedlings were given giberelin concentration of 10.000 ppm can improve seedling height reached 91,30cm. Key words :palm oil seedling, foliar fertilizer, gibberellins